Teachers' Dispositional Mindfulness and Well‐Being and Their Connection to Decentering and Teacher–Student Relationships - Maoz, Liat Ben‐Uriel; Lavy, Shiri; Berkovich‐Ohana, Aviva (Psychology in the schools, 2025)
ABSTRACT This longitudinal, two‐wave study builds on the mindful self in school relationships (MSSR) model, examining the link between dispositional mindfulness and teacher well‐being over time, and the roles of decentering and teacher–student relationships (TSRs) as potential mediators. It posits that dispositional mindfulness facilitates a reduction in self‐centered psychological processing that hampers well‐being while promoting teachers' ability to create positive, effective TSRs that contribute to their well‐being. Sixty‐two elementary school teachers were surveyed at the beginning (T1) and end (T2) of the 2019–2020 school year to evaluate their levels of dispositional mindfulness, decentering, well‐being, as well as the quality of their TSRs. The results supported the expected positive correlation between teachers' mindfulness at T1 and their well‐being at T2. Contrary to expectations, decentering did not act as a mediator between mindfulness at T1 and well‐being at T2. However, as predicted, TSRs significantly mediated the link between teachers' mindfulness at T1 and well‐being at T2. These outcomes highlight the potential impact of dispositional mindfulness on teachers' well‐being, possibly via its contribution to teachers' relationships with their students. The study contributes to the theoretical understanding of dispositional mindfulness in educational settings. Summary Dispositional mindfulness at the beginning of the school year predicted higher levels of teacher well‐being at the end of the year. Teacher–student relationships mediated the link between dispositional mindfulness and teacher well‐being. These effects were observed even without a formal intervention, highlighting the practical potential of dispositional mindfulness in day‐to‐day functioning within the school setting.